The 2021 WHO Classification of Tumors of the Pleura: Advances Since the 2015 Classification - Sauter, Jennifer L.; Dacic, Sanja; Galateau-Salle, Francoise; Attanoos, Richard L.; Butnor, Kelly J.; Churg, Andrew; Husain, Aliya N.; Kadota, Kyuichi; Khoor, Andras; Nicholson, Andrew G.; Roggli, Victor; Schmitt, Fernando; et al. (Journal of thoracic oncology, 2022)
Substantial changes in the 2021 WHO Classification of Tumors of the Pleura and Pericardium since the 2015 WHO Classification include the following: (1) pleural and pericardial tumors have been combined in one chapter whereas in the 2015 WHO, pericardial tumors were classified with cardiac tumors; (2) well-differentiated papillary mesothelioma has been renamed well-differentiated papillary mesothelial tumor given growing evidence that these tumors exhibit relatively indolent behavior; (3) localized and diffuse mesothelioma no longer include the term “malignant” as a prefix; (4) mesothelioma in situ has been added to the 2021 classification because these lesions can now be recognized by loss of BAP1 and/or MTAP by immunohistochemistry and/or CDKN2A homozygous deletion by fluorescence in situ hybridization; (5) the three main histologic subtypes (i.e., epithelioid, biphasic, and sarcomatoid) remain the same but architectural patterns and cytologic and stromal features are more formally incorporated into the 2021 classification on the basis of their prognostic significance; (6) nuclear grading for epithelioid diffuse mesothelioma is introduced, and it is recommended to record this and other histologically prognostic features in pathology reports; (7) BAP1, EZH2, and MTAP immunohistochemistry have been found to be useful in separating benign mesothelial proliferations from mesothelioma; (8) biphasic mesothelioma can be diagnosed in small biopsies having both epithelioid and sarcomatoid components even if the amount of one component is less than 10%; and (9) the most frequently altered genes in diffuse pleural mesothelioma include BAP1, CDKN2A, NF2, TP53, SETD2, and SETDB1.